2017
DOI: 10.1016/j.ijid.2017.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Humoral immune profiling of mycobacterial antigen recognition in sarcoidosis and Löfgren’s syndrome using high-content peptide microarrays

Abstract: Specific IgG recognition patterns for M. tuberculosis antigens in sarcoidosis patients re-affirm mycobacterial involvement in sarcoidosis, providing biologically relevant targets for future studies pertaining to diagnostics and immunotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 38 publications
0
10
0
2
Order By: Relevance
“…Since the mechanism of action of CFA-induced granulomatosis is unclear, the CFA injection method is not commonly adopted. Mycobacterium tuberculosis (MTB), which may cause sarcoidosis (18, 19), was used to develop animal models of MTB-induced sarcoidosis. Drake et al found Mycobacterium 16S rRNA and rpoB sequences in sarcoidosis tissue specimens (20).…”
Section: Discussionmentioning
confidence: 99%
“…Since the mechanism of action of CFA-induced granulomatosis is unclear, the CFA injection method is not commonly adopted. Mycobacterium tuberculosis (MTB), which may cause sarcoidosis (18, 19), was used to develop animal models of MTB-induced sarcoidosis. Drake et al found Mycobacterium 16S rRNA and rpoB sequences in sarcoidosis tissue specimens (20).…”
Section: Discussionmentioning
confidence: 99%
“…While patients with PAP harboring ATP-binding cassette deficiency are prone to opportunistic lung infections (Goldschmidt et al, 2003; Borie et al, 2011), TB or mycobacterial infections in general, it has also been implicated in the pathogenesis of sarcoidosis (van Enschot and van Balkom, 2013; Ferrara et al, 2017), suggesting an overall impaired host defense involving pulmonary surfactant disbalance. Interestingly, ABCA1 loss in murine alveolar macrophages enhanced pro-inflammatory immune responses in the lung and clearance of bacterial infection (Draper et al, 2010), which requires well-designed studies in humans.…”
Section: Pulmonary Surfactants In the Context Of Lung Immunometabolismmentioning
confidence: 99%
“…В основе метода лежит анализ релеевского уширения, рассеянного на определенный угол лазерного луча на «свободно» диффундирующих в растворе рассеивателях. Достоинством способа ДСР является то, что это точный диффузиометрический метод, позволяющий определить иммунные комплексы больших размеров -от единиц нанометров до десятков микрон, что позволяет без внесения внешних возмущающих воздействий получать информацию о распределении иммунных комплексов по размерам в биологических жидкостях [8,12,17]. Уникальность метода динамического светорассеяния заключается в возможности регистрации образования макромолекулярных комплексов в сложных биологических системах, не прибегая к фракционированию или каким-либо другим процедурам, нарушающим нативные условия, в которых происходит комлексообразование, что позволяет получать более детальную информацию [7].…”
Section: т 21 №unclassified
“…Недавние исследования показали ведущую роль иммунологических нарушений в развитии саркоидоза [12,14,15,16]. Роль сывороточных иммуноглобулинов в формировании гранулемы до конца не ясна, возможно, их участие заключается в формировании гранулем путем присоединения к иммунным комплексам.…”
Section: Introductionunclassified